Single nucleotide polymorphism C994g of the cytochrome P450 gene possess pleiotropic effects in Bos taurus, L. - Fedota, Olena; Puzik, Nina; Skrypkina, Inessa; Babalyan, Volodymyr; Mitiohlo, Larysa; Ruban, Serhii; Belyaev, Serhii; Borshch, Oleksandr O.; Borshch, Oleksandr V. (Acta Biologica Szegediensis, 2022)
The chronic consumption of mycotoxin-contaminated forage tends to the weight loss of young cattle, decreasing the reproductive success of adult animals, milk yield, and tolerance to high temperatures. The aim of this paper was to study the eff ects of the SNP C994G in the CYP3A28 gene on the productive and reproductive characteristics of dairy and beef breeds. Cows were measured by body weight dynamics, exterior, reproduction, milk production traits, bone mineral density, bulls were analyzed estimating their progeny traits. Dairy cows received dietary betaine supplement with the measurement of homocysteine levels. Molecular genetic was performed by PCR-RFLP method. The effects of SNP C994G were shown in relation to the udder size, the constitution and birth weight of Abredin-Angus cows, as well as the fat and protein content of Ukrainian Red-and-White Dairy cows milk. The higher sensitivity of the GG genotype to less homocysteine level after the addition of betaine was shown. Given the identifi ed correspondence, pleiotropic eff ects of CYP3A28 gene can be concluded. A microscopic analysis of forage supported the findings in relation to greater efficiency of the CC genotype under conditions of low mycotoxins contamination, to which CYP3A28 is selective.